APPLICATION OF GOOD CORPORATE GOVERNANCE IN PT. UNILEVER INDONESIA - Desi Eka Wati, Vebina (Dinasti Publisher, 2020)
Good Corporate Governance is corporate governance that explains the relationships between various participants in the company that determine the direction of the company's performance. Good corporate governance is corporate governance that explains the relationship of the parties participating in the management and performance of the company. Implementation of good governance principles is considered to have a positive impact on the company. Seeing the many achievements achieved by PT. Unilever Indonesia is primarily an award for GCG so researchers are interested in examining how it is applied and the constraints experienced. From the results of this study it can be seen that the application of GCG principles in the internal environment of PT. Unilever Indonesia has been going well, although sometimes it collides with changes that occur in the internal environment so that there are adjustments that must be made by all employees. The research method used is descriptive qualitative. Qualitative descriptive writing is writing that seeks to explain the current problem solving based on data, present data, analyze and interorete.